-2-8u=-3-9u-5

Simple and best practice solution for -2-8u=-3-9u-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2-8u=-3-9u-5 equation:


Simplifying
-2 + -8u = -3 + -9u + -5

Reorder the terms:
-2 + -8u = -3 + -5 + -9u

Combine like terms: -3 + -5 = -8
-2 + -8u = -8 + -9u

Solving
-2 + -8u = -8 + -9u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '9u' to each side of the equation.
-2 + -8u + 9u = -8 + -9u + 9u

Combine like terms: -8u + 9u = 1u
-2 + 1u = -8 + -9u + 9u

Combine like terms: -9u + 9u = 0
-2 + 1u = -8 + 0
-2 + 1u = -8

Add '2' to each side of the equation.
-2 + 2 + 1u = -8 + 2

Combine like terms: -2 + 2 = 0
0 + 1u = -8 + 2
1u = -8 + 2

Combine like terms: -8 + 2 = -6
1u = -6

Divide each side by '1'.
u = -6

Simplifying
u = -6

See similar equations:

| -x+8y=-14 | | -9-3f=1-8f | | 2w+2*(3w)=112 | | -40=-4(x+6) | | 4m+5n=13 | | 8r-6=7r | | 9x^2+4x+5=0 | | (13y)(8x+y)=(20x+3y) | | 5x^2+9x=10 | | -8-5m=-6m | | 18.25x-10.5x=23.25 | | 1-x^2=17 | | 6x/12 | | 8-6j=-8j | | x-19=5x+5 | | -67+2.5x= | | (7x-32)+(5x-27)=(9x-8) | | -20x+20y=-20 | | -5-4z=-5z+5 | | x/2-12=4 | | z^4+0.5z+1=0 | | (13x-11)+(4x+1)=(18x-15) | | 5k=4K-6 | | -3+10h=7h+6 | | (9x-8)+x=180 | | (3a+2)=-8 | | -9x+y=-22 | | 8b+8=6b | | x+3x-4=6 | | 2lne^5=y | | 7x+54+42=180 | | 0.60x=12 |

Equations solver categories